Hizbut Tahrir Indonesia’s View toward Democracy and Nation State and Its Implication in Indonesian Democracy - Mujahiduddin Mujahiduddin (Universitas Islam Negeri Alauddin Makassar, 2012)
This essay examines the emergence of HizbuutTahrirIndonesia (HTI) in the public sphere as an openly fundamentalist movement in the democratic era. HTI existed in Indonesia since the early 1980s. Its early presence was as a clandestine organization, because of the repressive state, but after 2000 it transformed itself into as an open Islamist movement. The fall of Suharto and subsequent democratic transition eradicated political restrictions, providing oxygen for HTI to publicise its religious beliefs and political program. This essay focuses on HTI’s view on democracy and nation state notion. It demonstrates that conceptually HTI is not in line with democracy concept and practically it refuses to participate in electoral politics. This writing argues that the presence of HTI with its stance anti- democracy may hamper the process of consolidating democracy in Indonesia.